Integrated Information and Communication Media Based on Organization Goal-Oriented Requirement Engineering (OGORE) - Fransiskus Mario Hartono Tjiptabudi (Faculty of Computer Science Universitas Indonesia, 2023)
The BPD NTT pension fund is a company incorporated as a legal entity that manages and runs a pension benefit program for BPD NTT employees. In its current business process, BPD NTT does not yet have a capable media to accommodate the information and communication needs of participants and interested parties, as a business branding and service facility for the participants. The problem that occurs is in the need elicitation stage when developing the information and communication media. For example, if the development is carried out by applying the Global eXtreme Programming (GXP) model, in the exploration phase the Organizational Goal-Oriented Requirement Engineering (OGORE) method will be applied to elicit needs that base each activity on organizational goals. The results of the research are in the form of web-based information and communication media modeling based on IT goals which are described in various tasks equipped with actors and resources used as well as KPIs that are integrated into each goal.